Accepted Manuscripts (Quarterly Journal of Economics, 1986)
Accepted Manuscripts The Quarterly Journal of Economics, Volume 101, Issue 1, February 1986, Page 209, https://doi.org/10.1093/qje/101.1.209 Published: 01 February 1986